Exosomes as a potential therapeutic approach in osteoimmunology - Zhivodernikov, Ivan V.; Markina, Yuliya V.; Kirichenko, Tatiana V.; Popov, Mikhail A.; Markin, Alexander M. (Frontiers in Immunology, 2023)
Exosomes are natural extracellular vesicles that play a key role in inter-and intracellular communication. Currently they are considered as a promising therapeutic strategy for the treatment of various diseases. In osteoimmunology, exosomes can serve as biomarkers of bone homeostasis disorders and, at the same time, promising therapeutic agents with high stability in the biological environment, low immunogenicity and good bioavailability. In this review, we attempted to examine exosomes as natural mediators of intercellular communication, playing an essential role in the interaction of the immune system and bone tissue, based on an analysis of the PubMed database up to